A child is worried about heartburn: modern views on the problem and possibilities of non-pharmacological support - O.Yu. Belousova; N.V. Pavlenko; K.V. Voloshyn; I.G. Solodovnichenko; O.M. Вabadzhanian; O.V. Shutova; L.G. Voloshyna; O.B. Hanzii (Zaslavsky O.Yu., 2024)
Background. The relevance is associated with a significant spread of dyspeptic symptoms in children. On average, every third-fourth child with such symptoms complains of heartburn, which is a frequent reason for consulting a doctor. For the pediatric category of patients, not only the timely diagnosis and effective treatment of pathological conditions associated with heartburn are important, but also the awareness of the parents of our patients and the children themselves about the possibilities of providing adequate first aid, safe and effective use of effective non-medicinal means. The purpose: to study the clinical effectiveness of using the special drink ISOTA for the first aid and preliminary treatment of children with heartburn in non-erosive reflux disease, functional dyspepsia and a combination of these conditions (overlap of non-erosive gastroesophageal reflux disease and functional dyspepsia). Materials and methods. Design: a single-center, open-label, pilot clinical trial. Fifty-four children aged 7-18 years with heartburn and other dyspeptic complaints were under observation. The study included 2 stages. The diagnosis was verified by means of surveys (GERDQ and QOLRAD questionnaires) and the use of fibrogastroscopy, endoscopic pH-metry. The results were recorded in the developed individual patient card and statistically processed. Results. Results of the study presented in the corresponding section testify to the high effectiveness of using ISOTA to eliminate heartburn and reduce other dyspeptic symptoms, as well as to a reliable improvement in the psychoemotional state, general well-being and quality of life of patients. Conclusions. The obtained results make it possible to recommend a slightly carbonated hydrocarbonate-containing special drink developed in Ukraine for a long-term use in a treatment course or as needed, and prophylactically to prevent heartburn and other dyspeptic symptoms in children, taking into account the high profile of effectiveness, safety and good tolerability.